Spiritual midwifery - Gaskin, Ina May (Book Pub. Co., 2002)
Shares the birthing stories of women who chose to have their babies at home with the help of a midwife, provides information about the safety of techniques used in the hospital before and after birth, discusses postpartum depression and maternal death, and includes resources for doulas, birth centers, and other organizations.